Pengaruh Motivasi Kerja, Budaya Organisasi dan Kualitas Kehidupan Kerja terhadap Kinerja Karyawan (Universitas Negeri Semarang, 2015)
The purpose of this research is to know the influence of work motivation, organizational culture, and quality of work life employee on performance of PT Asaputex Jaya. Population and sample the study that all employees of PT Asaputex Jaya Tegal on the field finishing as many as 73 people. The sampling technique in the study is using a sampling of satutared. Methods of collection data using interview and questionnaire. Method of data analysis using multiple linear regression analysis with IBM SPSS Statistics program 21. The results showed that there was no influence between work motivation toward performance, there is the influence of organizational culture on performance, and there is no effect quality of work life on the performance. The conclusions this study are the work motivation has no significance effect on the employee performance, the organizational culture has positive and significant effect on the employee performance, and the quality of work life has significant positive effect on the employee performance.